COLOR CHANGES COMPARISON OF HEAT CURED TYPE ACRYLIC RESIN IN IMMERSION OF ALKALINE PEROXIDES SOLUTION AND CELERY EXTRACT (APIUM GRAVEOLENS L.) 75% - Puspitasari, Dewi; Saputera, Debby; Ayu Soraya, Imelia (Dentino, 2017)
ABSTRACKBackground: Heat cured-type acrylic resin is the most widely used as denture base. denture base that is less clean may result in the accumulation of microorganisms. The chemical denture cleanser solution such as alkaline peroxide and 75% celery extract are able to clean and inhibits the growth of fungi and bacteria. The disadvantage of acrylic resin is water absorbing includes denture cleanser solution that may result in color change of resin. Purpose: The study is aim at measuring the color change differences of heat cured-type acrylic resin in immersion of alkaline peroxide solution and 75% celery extract (Apium graveolens L.) as denture cleanser for 5 days and 15 days. Method: The study was a true experimental research with control group design pre-test and post-test, using sample of 2mm thickness and 15mm diameters based on ADA specification no 17. Total samples were 36, divided into 6 treatment groups that is immersed in alkalin peroxide solution, 75% celery extract and aquadest for 5 and 15 days. The color change was measured using tools spectrometer,101 photo detector and microvolt digital. The statistical test was using One-way ANOVA and Post Hoc Bonferroni with <0.05 significance. Result: There is significance differences of color change acrylic resin in immersion of alkaline peroxide solution and 75% celery extract for 5 days and 15 days. Mean value of color change alkalin peroxide solution (0,48mv), aquadest (0,33mv) and celery extract 75% (1,36mv) for 5 days, alkaline peroxide solution (0,50mv), aquadest (0,39mv) and 75% celery extract (1,00mv) for 15 days. Conclusion: The immersion in 75% celery extract (Apium graveolens L.) 5 days and 15 days had greater value in color change than alkaline peroxide solution.Keywords: Heat cured type Acrylic resin, Alkaline peroxide, 75% celery extract (Apium graveolens L), Color Change.